Advances in date palm (Phoenix dactylifera L.) research programme in Morocco: A review (IASH Indian Journal of Arid Horticulture, 2026)
Date palm (Phoenix dactylifera L.) is a woody monocot tree producing fruits with high nutritional and economic importance. Currently, date production suffers from several biotic and abiotic stresses that reduce its profitability and menace its productivity. Moreover, climate change due to global warming has negatively affected crop production worldwide including dates. Despite the high resilience of the date palm tree, there is a need to develop new cultivars that are higher yielding and possess highly valued agronomic traits, such as fruit quality, disease and pest resistance and tolerance of extreme environmental conditions. In order to address this uncomfortable situation, Morocco has undertaken a huge research program for control of Bayoud disease basically, based on selection or creation of tolerant genotypes. To this end, several breeding approaches have been pursued, including: mass selection, cross breeding and induced mutagenesis. Obtained results have permitted to select many tolerant genotypes to Bayoud disease including cv. Nejda that has been largely propagated. In order to rehabilitate devastated palm groves with selected genotypes, plant tissue culture techniques were developed including organogenesis and somatic embryogenesis both from offshoot shoot tips or inflorescence plant material. Developed propagation technologies were transferred to private labs for mass propagation of date palm. Collaboration between public and private sectors has permitted production of three million vitro plants up to 2020 and a new plant production program is launched to produce five million plants in the horizon of 2030. Overall, the major research aspects of the national strategy to develop date palm sector in Morocco are presented.